Affinity proteomics data for Venous thromboembolism biomarker study (VEBIOS) rescreening. - Smith, Philip; Kotol, David; Farm, Maria; Schwenk, Jochen; Uhlén, Mathias; Magnusson, Maria; Morange, Pierre Emmanuel; Trégouët, David Alexandre; Antovic, Jovan; Butler, Lynn Marie; Edfors Arfwidsson, Fredrik; Iglesias Mareque, Maria Jesus; et al. (Royal Institute of Technology, 2026)
Affinity proteomics data for Venous thromboembolism biomarker study (VEBIOS) rescreening

This dataset contain two documents with log-transformed and normalised MFI values from an affinity proteomics screenings in citrate plasma from individuals with venous thromboembolism.

The dataset 1 contains plasma profile data for the individual with suspected acute venous thrombosis.

Dataset 2 includes the plasma profile data for the individuals analyzed after a frist-time venous thrombosis along with the corresponding control subjects.
Keywords: Cardiovascular medicine and haematology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Cardiology and Cardiovascular Disease; Kardiologi och kardiovaskulära sjukdomar